Digitalisasi Aktivitas Jual Beli di Masyarakat: Perspektif Teori Perubahan Sosial - Ely Laily Bunga Rahayu; Nur Syam (Jayapangus Press, 2021)
This study discusses buying and selling activities in the present context. A process of changing buying and selling activities that were originally traditional or conventional to digital. Due to the rapid development of technology, it is finally making changes to buying and selling activities that were originally by way of direct transactions face to face between sellers and buyers, now sellers and buyers only transact via virtual or online using certain platforms. This study uses a qualitative research method, where the researcher aims to describe and analyze changes in people's behavior related to buying and selling activities from an offline system to an online one. Social change in society is not a result or a product but a process. This change process is of course the result of an agreement or joint decision taken by an individual or a community group. The decisions taken are of course in accordance with the wishes or expectations of the group so that social change can be realized.